2011
DOI: 10.1590/s0066-782x2011005000032
|View full text |Cite
|
Sign up to set email alerts
|

Proteína C-reativa e prognóstico em síndromes coronarianas agudas: revisão sistemática e metanálise

Abstract: Despite the association between high-sensitivity C-reactive protein (CRP) and recurrent events in non-ST elevation acute coronary syndromes (ACS), routine determination of this marker has not been recommended.In order to verify whether the current scientific evidence justifies the inclusion of CRP for risk stratification at hospital admission of patients with ACS, we carried out a systematic review and meta-analysis of the studies indexed in MEDLINE, SciELO or LILACS, with the following inclusion criteria: pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Apesar disso, os achados reforçam a utilidade da PCR e da PCR-us em diferentes doenças crônicas não transmissíveis. Sendo que a presente revisão sistemática amplia e atualiza outras 4 revisões sistemáticas realizadas por Correia e Esteves (2011), Laks et al, (2011), Cardoso et al (2012), e Choi, Joseph e Pilote (2013) 15,[53][54][55] .…”
Section: Discussionunclassified
“…Apesar disso, os achados reforçam a utilidade da PCR e da PCR-us em diferentes doenças crônicas não transmissíveis. Sendo que a presente revisão sistemática amplia e atualiza outras 4 revisões sistemáticas realizadas por Correia e Esteves (2011), Laks et al, (2011), Cardoso et al (2012), e Choi, Joseph e Pilote (2013) 15,[53][54][55] .…”
Section: Discussionunclassified
“…In the 2000s, several studies were published in journals of high impact, favorable to the prognostic value of CRP in patients with ACS. These studies were analyzed as a systematic review and meta-analysis by our group, which was published in 2010 3 . Unlike the enthusiastic attitude of some authors, our review concluded that there was no conclusive evidence of the incremental prognostic value of CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Among these markers, High-Sensitivity C-Reactive Protein (hs-CRP) is the best studied as a risk predictor in clinical practice 2 . Actually, several studies have shown an association between CRP and cardiovascular risk in patients with ACS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A recently published systematic review found a positive association between elevated hs-CRP during ACS (with cutoff values between 10 and 15 mg/L) and long-term cardiovascular events, with a multivariate odds ratio of 2.5 (95% confidence interval: 1.8-3.4). The predictive power for short-term events was inconsistent, revealing heterogeneity in the results 14 . According to this same study, only 2 of the 19 prospective studies included in the analysis assessed the additional discriminatory ability for new events in multivariate models revealing opposite and, therefore, inconsistent results.…”
Section: Biomarkers In Chronic Coronary Atherosclerotic Diseasementioning
confidence: 99%